A pan-cancer analysis of the oncogenic role of N-acetyltransferase 8 like in human cancer - Jiamin Chen; Fanglin Shao; Shuxia Zhang; Youliang Qian; Mei Chen (Discover Oncology)
Abstract Background N-Acetyltransferase 8 Like (NAT8L) inhibits natural killer (NK)/T-cell cytotoxicity by impairing the formation of the immunological synapse via N-acetylaspartate (NAA). Existing research has predominantly focused on the metabolic functions of NAT8L, particularly in adipose tissues and myelination in the brain. However, in contrast to other N-acetyltransferases such as NAT1 and NAT2, the role of NAT8L in cancer has been less extensively studied. In this study, we conducted a comprehensive pan-cancer analysis to investigate the carcinogenic role of NAT8L in human cancers. Methods We utilized the standardized TCGA pan-cancer dataset to analyze differential expression, clinical prognosis, gene mutation, immune infiltration, epigenetic modification, tumor stemness, and heterogeneity. Additionally, we evaluated the sensitivity of NAT8L to small molecule drugs using the GDSC and CTRP databases. Results In this study, we identified that NAT8L expression was upregulated in 6 cancers and downregulated in 12 compared to normal tissues. We analyzed its prognostic value in 5 tumor types (KIRP, COAD, COADREAD, GBMLGG, LUSC) and found correlations with overall survival (OS), disease-specific survival (DSS), and progression-free interval (PFI). Furthermore, NAT8L expression was significantly correlated with levels of most immune checkpoints, immunomodulators, and immune cell infiltration. The mutation frequencies for bladder cancer (BLCA), glioblastoma multiforme and glioma (GBMLGG), lower-grade glioma (LGG), and KIRP were 1.2%, 0.9%, 0.8%, and 0.4%, respectively. Conclusion Our findings suggest that NAT8L may serve as a potential prognostic marker and therapeutic target across a variety of cancers, particularly in KIRP, COAD, COADREAD, GBMLGG, and lung squamous cell carcinoma (LUSC).